2014
DOI: 10.7863/ultra.33.8.1461
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Distal Biceps Tendon Injections

Abstract: Sonographically guided distal biceps peritendinous/intratendinous injections are feasible and therefore may play a role in the management of patients presenting with distal biceps tendinopathy/bursopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Specifically, with the anterior approach the operator must safely navigate around the brachial artery, median nerve, and lateral antebrachial cutaneous nerve, all of which lie in close proximity to the biceps tendon in that view (Figure 4). This concern has been demonstrated in the aforementioned cadaver study in which the experienced sonographer [8] noted a brachial artery injury when experimenting with an anterior injection approach to this area. By using the technique we describe in this report, these neurovascular structures are avoided.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Specifically, with the anterior approach the operator must safely navigate around the brachial artery, median nerve, and lateral antebrachial cutaneous nerve, all of which lie in close proximity to the biceps tendon in that view (Figure 4). This concern has been demonstrated in the aforementioned cadaver study in which the experienced sonographer [8] noted a brachial artery injury when experimenting with an anterior injection approach to this area. By using the technique we describe in this report, these neurovascular structures are avoided.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, use of the US-guided approach with a live subject has not previously been described in the literature; however, this approach has been studied in cadavers [8]. In that study the authors injected 18 unembalmed cadaveric elbows from different approaches, which included an in-plane posterior approach similar to the technique we described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several viable options described for infiltration with ultrasound guidance. Sellon et al [1] found a high success rate for sonographically guided peritendinous and intratendinous infiltration of the distal biceps tendon through multiple approaches. All of their peritendinous injections were successful, and 94% of their intratendinous injections were successful.…”
Section: Discussionmentioning
confidence: 99%
“…proaches available for infiltration around the biceps tendon [1]. Some perform the injection manually without ultrasound guidance; others use ultrasound guidance to determine the location of the tip of the needle.…”
mentioning
confidence: 99%